ANALISIS PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN DEVIDEN PAYOUT RATIO SEBAGAI VARIABEL INTERVENING - Sabarudin; La Sudarman; Firdaus (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2021)
Abstract: This study aims to analysis influence profitability on firm’s value with dividend payout as intervening variable. Sample to be studied in this research is 21 (twenty one) firm’s which have to stay for 5 years in LQ45 index in Indonesian Stock Exchange for period 2009 – 2013. Sampling technique was used is purposive sampling. Method of analysis used multiple regression analysis with SPSS 20. Finding of study is profitability, dividend payout affect significant positive on firm’s value and profitability affect significant positive on dividend payout. Dividend payout still have a role to increase firm’s value because dividend payout affect significant positif directly on firm’s value Keywords : profitability, financial leverage, dividend payout, firm value